Ukraine and the art of strategy - Freedman, Lawrence, 1948- (Oxford University Press., 2019)
Présentation de l'éditeur : "In Ukraine and the Art of Strategy, Sir Lawrence Freedman provides an account of the origins and course of the Russia-Ukraine conflict through the lens of the theory and practice of strategy. That is, he explores Putin's near, medium, and long-term strategies when he decided to initiate the conflict. How successful has he been ? In contrast to many who see Putin as a master operator who has resuscitated a supine Russia against all odds, Freedman is less impressed with his strategic acumen in terms of the long-term fallout. By exploring concepts such as coercive diplomacy, limited war, escalation and information operations, Freedman brings the story up to the present, where a low-level conflict between Ukrainian and breakaway rebel forces in the east grinds on, and illuminates the external challenges faced by the governments' involved."